Real-World Clinical and Economic Outcomes in Selected Immune-Related Adverse Events Among Patients with Cancer Receiving Immune Checkpoint Inhibitors. (24th August 2021) - Zheng, Ying; Kim, Ruth; Yu, Ting; Gayle, Julie A.; Wassel, Christina L.; Dreyfus, Jill; Phatak, Hemant; George, Saby
Abstract : Background: With increased use of immune checkpoint inhibitors (ICIs) among patients with cancer, there is substantial interest in understanding clinical and economic outcomes and management of immune-related adverse events (irAEs). Patients, Materials, and Methods: A retrospective study was conducted using Premier Healthcare Database, a U.S. national hospital discharge database, from March 1, 2015, through December 31, 2017. The database comprises more than 880 million inpatient and hospital-based outpatient encounters, with more than 200 million unique patients reported by 966 hospitals. Patients with four solid tumors known to benefit from ICI therapy were included. The list of irAEs assessed was defined a priori per American Society of Clinical Oncology clinical guidelines for irAE management. Baseline irAE-related inpatient and outpatient visits were defined as the first inpatient or hospital-based outpatient visit with discharge diagnosis of any irAE of interest following confirmed ICI usage within 90 days prior to the baseline visit. Patients were followed for 90 days after baseline irAE-related inpatient discharge date or outpatient visit date to assess irAE-related inpatient admissions, all-cause in-hospital mortality, ICI reinitiation, and to determine costs and health care resource utilization. Results: Records from 673, 957 patients with four tumor types were reviewed for ICI therapy. Of 13, 030 patients receiving ICIs, approximately 40% experienced at least one irAE, with a total of 10, 121 irAEs occurring within 90 days of the ICI visit. The most frequent (>1, 000 events) irAEs were anemia, impaired ventricular function with heart failure and vasculitis, thrombocytopenia, thyroid conditions, and peripheral edema. As might be expected, compared with those with baseline irAE-related outpatient visits, patients with baseline irAE-related inpatient visits had a significantly higher percentage of irAE-related inpatient admissions (23% vs. 14%) and all-cause in-hospital mortality (22% vs. 6%) and lower reinitiation of ICI therapy (31% vs. 71%). Baseline irAE-related inpatient visits had significantly higher mean costs ($29, 477 vs. $5, 718) with longer hospital stays (12.6 vs. 7.8 days). Conclusion: Findings from a U.S. national hospital discharge database suggest that irAEs in patients treated with ICIs are common, occur in multiples and with greater frequency in those with pre-existing comorbidities. Those with inpatient admissions have poorer outcomes. Implications for Practice: The present work addressed the knowledge gap in understanding real-world outcomes of immune-related adverse events (irAEs) associated with immune checkpoint inhibitors (ICIs). Patients who experienced irAEs had significantly higher baseline comorbidities and were more likely to have immune-related or immune-compromised comorbid conditions. Patients with baseline irAE-related hospitalizations were more likely to be rehospitalized and to experience in-hospital mortality and less likely to reinitiate ICI treatment. Real-world patients are more diverse than clinical trials, and clinicians should consider both the efficacy and safety profile of ICI treatments, especially for patients with comorbidity conditions. Close monitoring is needed after patients have experienced an irAE. Abstract : This large real-world evidence study assessed the prevalence of immune-related adverse events among patients who received immune checkpoint inhibitors and associated clinical and economic outcomes